Molds and More: Rare Fungal Infections in Preterm Infants <24 Weeks of Gestation. Issue 4 (23rd November 2021) - Mehler, Katrin; Cornely, Oliver; Seifert, Harald; Zweigner, Janine; Janssen, Saskia; Oberthuer, André
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Extreme immature infants are at an increased risk of fungal infection due to immaturity of the skin barrier and the immune system. Besides Candida infections, in particular, Aspergillus may cause life-threatening diseases in preterm infants. Frequently, Aspergillus primarily affects the skin and may cause extensive damage. Methods: We searched our hospital database for fungal infections other than Candida in preterm infants treated between 2015 and 2020 at our level III neonatal intensive care unit of the University Hospital of Cologne. Results: In total, 13 preterm infants were identified. Of these, 11 had cutaneous Aspergillosis, one infant had severe enterocolitis caused by Aspergillus and Rhizopus and one had invasive intraabdominal Trichosporon mucoides infection. All infants were born <24 weeks of gestation, were delivered due to premature labor or chorioamnionitis, and had received prenatal steroids and/or hydrocortisone. Voriconazole and liposomal Amphotericin B were first-line treatments and the length of treatment varied between 3 and 148 days. Two infants died associated with severe infection. Liver toxicity was observed in six infants treated with Voriconazole. Therapeutic drug management for Voriconazole was performed in four infants. Target levels were not achieved by the doses that are recommended. Conclusions: Rare fungal infections, predominantly cutaneous Aspergillosis affects the most immature preterm infants and may cause severe disease. Treatment with Voriconazole has a high rate of liver toxicity and target levels are difficult to achieve in extremely immature infants.